High-efficiency RNA-based reprogramming of human primary fibroblasts - Igor Kogut (Nature Portfolio, 2018)
Induced pluripotent stem cells (iPSCs) have potential for regenerative medicine applications, but are generated with very low efficiency. Here, the authors show highly efficient reprogramming of human primary fibroblasts to iPSCs via the synergistic activity of synthetic modified mRNAs, mature miRNA mimics, and optimized culture methods.